URGENSI PEMBINAAN KARAKTER RELIGIUS BAGI MUALAF DI KOTA SINGKAWANG - Asrip Widodo; Suparman Syukur; Abu Hapsin (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: The development of religious character for converts is very important so that their Islamic faith becomes perfect (kāffah). Perfection is marked by leaving the old religious teachings and practicing Islamic teachings in the fields of faith, worship, morals, muamalah, being able to read and memorize the verses of the Qur'an. This study is intended to answer the question: Why is religious character building needed for converts in Singkawang City? This problem is studied through qualitative field research. Research location as a source of data through free interviews, structured interviews, participant observation, and documentation study. All data were analyzed using a case study approach with descriptive-analytical techniques because: the research problem is holistic, complicated and interpretive. This study shows that: The development of religious character for converts in Singkawang City needs to be done because the status of converts itself requires guidance because converts are people who leave their ingrained beliefs, religions and life behaviors and replace them with religions that are already ingrained. new namely Islam; because of the problems of converts that need to be resolved, because converts after becoming Muslims encounter many problems, not only religious problems, converts also encounter various other problems including negative responses from family, insults, isolation to conflicts and acts of violence from family members, it is still difficult. abandoning some of the traditions and aspects of their old religious teachings, as well as Islamic religious guidance that they have not yet received maximally; to meet the needs of converts; and to demonstrate a brotherly commitment. Keywords: Development, Character, Religious, Converts